Crown and root lengths of incisors, canines, and premolars measured by cone-beam computed tomography in patients with malocclusions - Kim, Seon-Young; Lim, Sung-Hoon; Gang, Sung-Nam; Kim, Hee-Jin (Korean journal of orthodontics (2012), 2013)
The purposes of this study were to determine the accuracy of crown and root length measurements of premolars using cone-beam computed tomography (CBCT) and to generate reference CBCT-based data on incisor, canine, and premolar lengths in patients with malocclusions. Imaging was performed using a CBCT scanner with a 0.292-mm voxel size and 12-bit grayscale. The CBCT-based length measurements were compared with direct measurements of 94 subsequently extracted premolars without metal restorations using the paired t-test. Furthermore, the crown and root lengths of incisors, canines, and premolars in 62 Korean patients with malocclusions were measured using CBCT, and Pearson's correlation coefficients were calculated to examine the relationship between the crown and root length measurements of each tooth type. The differences between the CBCT-based and direct measurements of the extracted premolars were not significant, with 95% limits of agreement of -0.90 to 0.90 mm for crown length and -1.23 to 1.18 mm for root length. Weak positive correlations between the crown and root length measurements were observed for the mandibular canine and premolars. The CBCT-based measurements showed a wider range of limits of agreements for root length than for crown length. The CBCT-based data can be used as a reference for evaluating root length and resorption of teeth without metal restorations in patients with malocclusions.